Predictors of major lower limb amputation among type II diabetic patients admitted for diabetic foot problems - Mohd Yusof, Nazri; Ab Rahman, Jamalludin; Zulkifly, Ahmad Hafiz; Che Ahmad, Aminudin; Khalid, Kamarul Ariffin; Sulong, Ahmad Fadzli; Vijayasingham, Naveen (Singapore Medical Association, 2015)
Diabetes mellitus (DM) is the most common cause of amputations in Malaysia. This study aimed to identify the predictive factors for major lower limb amputation among patients with type 2 DM (T2DM) who were admitted to a hospital, in order to reduce its likelihood. METHODS This cross-sectional study involved 218 patients with T2DM who were admitted to Hospital Tengku Ampuan Afzan, Kuantan, Malaysia, for diabetic foot problems from June 2011 to July 2012. A form was developed to document the patients’ profiles, comorbidities, complications, investigations, treatment and clinical outcomes. The predictors for major lower limb amputations were determined using univariate and stepwise logistic regression analysis. RESULTS A total of 31 patients underwent major lower limb amputations (25 transtibial, 6 transfemoral). The following factors were found to be associated with the incidence of major lower limb amputations: T2DM duration ≥ 10 years, diabetic neuropathy, diabetic nephropathy, presentation with gangrene, diabetic foot conditions of Wagner grade 4 or 5, and necrotising fasciitis. Patients who underwent major amputations had significantly lower haemoglobin and albumin levels, and higher total white blood cell counts, erythrocyte sedimentation rates, and C-reactive protein, urea and creatinine levels. However, only T2DM duration ≥ 10 years, positive bacterial culture and albumin levels were significant on stepwise logistic regression analysis. CONCLUSION T2DM duration ≥ 10 years, positive bacterial culture and low albumin levels were found to be significant predictive factors for major lower limb amputation among patients with T2DM admitted for diabetic foot problems.